Sex offender treatment : a case study approach to issues and interventions - Wilcox, D. T. (Daniel T.); Garrett, Tanya; Harkins, Leigh (Malden, MA : Wiley-Blackwell, 2015)
Sex Offender Treatment is an innovative case study-based guide to the treatment of sexual offenders, offering direct access to the insights and experience of experts in the field. The book describes case formulations, assessment processes, and treatment undertaken with specific sexual offender types. Takes an innovative case study approach to sexual offender assessment and treatment, sharing practical insights and real-world experience in a challenging fieldCoverage is organized by key offender populations and includes bipolar offenders, child sexual abusers, Internet offenders, psychopathic.